Enterovirus 2Apro Cleavage of the YTHDF m6A Readers Implicates YTHDF3 as a Mediator of Type I Interferon-Driven JAK/STAT Signaling - Kastan, Jonathan P; Tremblay, Martine W; Brown, Michael C; Trimarco, Joseph D; Dobrikova, Elena Y; Dobrikov, Mikhail I; Gromeier, Matthias (mBio, 2021)
Enteroviruses (EV) deploy two proteases that mediate viral polyprotein cleavage and host cell manipulation. Here, we report that EV 2A proteases cleave all three members of the YTHDF protein family, cytosolic N6-methyladenosine (m6A) “readers” that regulate target mRNA fate. YTHDF protein cleavage occurs very early during infection, before viral translation is detected or cytopathogenic effects are observed. Preemptive YTHDF protein depletion enhanced viral translation and replication but only in cells with restrained viral translation, signs of inefficient 2A protease activity, and protective innate host immune responses. This effect corresponded with repression of interferon (IFN)-stimulated gene (ISG) induction, while type I/III IFN production was not significantly altered. Moreover, YTHDF3 depletion impaired JAK/STAT signaling in cells treated with type I, but not type II, IFN. YTHDF3 depletion’s stimulatory effect on viral dynamics was dampened by JAK/STAT blockade and enhanced by type I IFN pretreatment of cells. We propose that EV 2A proteases cleave YTHDF proteins to antagonize ISG induction in infected cells. IMPORTANCE It is believed that ∼7,000 messenger RNAs (mRNAs) are subject to N6-methyladenosine modification. The biological significance of this remains mysterious. The YTHDF m6A readers are three related proteins with high affinity for m6A-modified mRNA, yet their biological functions remain obscure. We discovered that polio/enteroviruses elicit very early proteolysis of YTHDF1 to 3 in infected cells. Our research demonstrates that YTHDF3 acts as a positive regulator of antiviral JAK/STAT signaling in response to positive single-strand RNA virus infection, enabling type I interferon (IFN)-mediated gene regulatory programs to unfurl in infected cells. Our observation of viral degradation of the YTHDF proteins demonstrates that they are key response modifiers in the innate antiviral immune response.